Effect of compliance with environmental regulations in the construction of public civil works, Cajamarca, Peru - Quinto Sanchez, Dulcet Lorena (2023)
Construction activities produce considerable environmental effects and have resulted in a growing demand to implement favorable environmental practices. In this sense, this research aimed to evaluate the effect of the level of compliance with environmental regulations in public civil works in the San Ignacio, Cajamarca, Peru district. Data were obtained through direct observation and structured interviews in 7 selected construction sites. The deductive and analytical method was used. As a result, the level of compliance was obtained. Work 4 had the highest rank, and works 2 and 5 had the lowest. Currently, all the works are in a similar range of compliance. The degree of association between the level of compliance with environmental regulations and the current state of the civil works indicates a probability of 0.0190, which shows that the low level of compliance with environmental regulations in the construction of public civil works in the district of San Ignacio generates a deterioration in the quality of the environment and increases the possibility of administrative sanctions.